Reliability and Validity of Feminist Identity Composite in Chinese Women - Liu, Yingjiang; Zheng, Yong (Frontiers in Psychology, 2019)
This study evaluated the psychometric properties of a Chinese form of the Feminist identity Composite (FIC). A total of 2,334 Chinese adult women completed the scale for this study. In study 1 (n = 875), exploratory analysis indicated six factors, Passive Acceptance (PA), Revelation (REV), Embeddedness/ Emanation (EE), Active Commitment (AC), and Synthesis (SYN), the latter of which was divided into two subscales (Femininity Synthesis and Autonomous Synthesis). In study 2 (n = 810), confirmatory factor analysis (CFA) was conducted with a different sample to examine the construct validity of the model obtained in study 1. In study 3 (n = 649), the convergent validity of FIC was examined via their relationship with willingness to engage in feminist behaviors and attitude towards trans-people. The results indicated that a new measurement with solid conceptual and psychometrically solid properties needs to be developed to assess Chinese women’s feminist identity.